ELECTRONIC MARKETING IN KURDISTAN REGION IRAQ: ISSUES AND CHALLENGES - Othman, Nasreen Kakil; Abdulrahman, Luqman Qader (International Journal of Psychosocial Rehabilitation, 2020)
After the wide spread of the Internet in the Kurdistan Region of Iraq and the increasing number of people who deal with the Internet purchasing has become an easy process at the same time enjoyable, yet remains a set of problems hindering the development of this type of sale and purchase.In this research, we prepared a special questionnaire that contains a set of questions and gave it to more than 150 people from different groups and specialties to find out their opinions on this subject.We took advantage of the data analysis program (SPSS). We collected and reached a set of conclusions then presented a set of suggestions to address the problems that’s faced by electronic marketing.Findings indicated that Electronic marketing is one of the main branches of public marketing, also called (digital marketing, or network marketing), which is the strategy used to regulate the methods of modern communication technology, by transforming the virtual marketing into reality, The important part of modern comprehensive marketing strategy is a significant type of marketing methods that aims to achieve its objectives online, also described as the process of applying the general principles of marketing science through the use of electronic media, especially use of network Internet.